2016
DOI: 10.22211/cejem/64965
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Density of Energetic Materials on the Basis of their Molecular Structures

Abstract: Abstract:The density of an energetic compound is an essential parameter for the assessment of its performance. A simple method based on quantitative structureproperty relationship (QSPR) has been developed to give an accurate prediction of the crystal density of more than 170 polynitroarenes, polynitroheteroarenes, nitroaliphatics, nitrate esters and nitramines as important classes of energetic compounds, by suitable molecular descriptors. The evaluation techniques included cross-validation, validation through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Rahimi et al. [15] used ANN and MLR models with five complex molecular descriptors for prediction of the density of 172 polynitroarenes, polynitroheteroarenes, nitroaliphatics, nitrate esters and nitramines at room temperature. It was found that the ANN model can give a more reliable prediction as compared to the MLR model.…”
Section: Different Methods For the Estimation Of The Densities Of Orgmentioning
confidence: 99%
“…Rahimi et al. [15] used ANN and MLR models with five complex molecular descriptors for prediction of the density of 172 polynitroarenes, polynitroheteroarenes, nitroaliphatics, nitrate esters and nitramines at room temperature. It was found that the ANN model can give a more reliable prediction as compared to the MLR model.…”
Section: Different Methods For the Estimation Of The Densities Of Orgmentioning
confidence: 99%
“…They have also found a simple method for calculating the detonation pressure of ideal and non-ideal explosives [30]. Rahimi et al [31] have estimated the densities of energetic materials on the basis of their molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…In QSPR, a relation will be found between property and basic molecular properties using advanced mathematic methods such as genetic algorithm and neural network. Basic molecular properties obtained from the chemical structure of compounds are called "molecular descriptors" (Rahimi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%